How to understand the rural in rural education? A documentary approach - Dueñas-García, German Dario; Espinel, Oscar (Universidad Pedagógica y Tecnológica de Colombia, 2021)
This article explores the conceptions of rural and rurality in rural education. The text focuses on the publications of the 2010 to 2020 years of the journal Praxis y Saber. At the same time, some theoretical references were used in order to broaden the instruments of understanding and inquiry. Thus, rurality was explored in a sociological context that compares development and education concerns; while rurality was approached as a broader and differentiated environment according to the experiences in different territories. The survey shows as categories issues such as the lack of relevance and investment in the rural sector and therefore in education -problems identified in the work of Fals Borda-; the differentiation that territories have in terms of culture and ways of life, which have not been sufficiently explored; and the existence of individual research projects concerned with providing alternatives, which, however, in their development are insufficient.